The Artistic Turn: A Manifesto - Coessens, Kathleen; Crispin, Darla; Douglas, Anne (Leuven Universitaire Pers Leuven, 2009)
Despite innovative developments in research in-and-through the arts in the past decade, the emergent field of artistic research remains controversial, and is accepted with varying degrees of enthusiasm in academic institutions. It is our contention that the challenges and opportunities presented by this burgeoning discipline may be better understood by re-emphasising the centrality of the artist. Through a study of the interrelationship between artistic fields and theories of knowledge, and through some consciously metaphorical readings, we examine the contexts within which artistic research has developed. Using this information as a means of interrogating both scientific and artistic research paradigms, and case studies concerning specific artist-researchers, the case is set out for a fresh paradigm an artistic turn. The aim is to create a field of meaning that may illuminate the most promising, though correspondingly problematic, aspects of artistic research: the essential ineffability of artistic creativity, and the consequent insufficiency of verbal and written accounts something which inevitably impacts upon the text presented here. Accordingly, the discourse articulated in this volume does not propose definitive approaches, but charts a constellation of ideas that outlines the new discipline and points to its manifold and open-ended possibilities.
Keywords: Artistic research